HUBUNGAN VARIABEL DEMOGRAFI DAN DIMENSI BUDAYA DENGAN PERILAKU KOMPLAIN WISATAWAN HOTEL BERBINTANG DI BALI - Jokohael, Nosahari Febrin; Sri Suprapti, Ni Wayan; Kerti Yasa, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This research was conducted to determine the relationship of demographic variable and cultural with complaints behavior of star hotels guest in Bali. Respondents in this study are 60 foreign guests and 60 domestic guests. This research uses consumer demographic and hofstede’s cultural dimensions to investigate the differences of foreigner and domestic complaining behavior. The analysis techniques used were various statistical methods such as frequency distribution, crosstab analysis and chi-square test. The result showed that from demographic variable, foreign guests with high income tend to make public complaint while domestic guests with low and medium income are likely to engage with private complaint. Meanwhile, from cultural dimension perspective, guests with low power distance, in an individualism culture and low uncertainty avoidance are tend to take public complaint while guests with high power distance, in a collectivism culture and high uncertainty avoidance are tend to take private action .